(untitled) (Baghdad Science Journal, 2013)
This study was conducted to test the effect of aqueous and alcoholic extracts for cyperus rotundus on the mitosis in tap roots of Allium cepa. the result of general an identical qualitative tests showed contains certain compounds that of crude aqueous and alcoholic extract, Used as five different concentrations of (10, 20.38, 56, 75) mg / ml for a period of four hours of treatment. After the chemical has been detected for some preliminary chemical compounds of the crude aqueous extract, while the alcoholic extract either phenol compound has been detected for phenols using several techniques included the use of thin layer chromatography TLC and measurement of disability factor RF and the degree of fusion and measurement of absorbance. The results showed that the crude aqueous extract and alcoholic extract and phenol their impact inhibitive as decreased normal division in all concentrations, where it decreased to 50% of the control treatment at the highest concentration also led all transcription to stop cells in metaphase at different rates and there were some chromosomal aberration including Bridges.